2013
DOI: 10.1021/nl402544n
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Gap Semiconducting Graphene from Nitrogen-Seeded SiC

Abstract: All carbon electronics based on graphene has been an elusive goal. For more than a decade, the inability to produce significant band-gaps in this material has prevented the development of graphene electronics. We demonstrate a new approach to produce semiconducting graphene that uses a submonolayer concentration of nitrogen on SiC sufficient to pin epitaxial graphene to the SiC interface as it grows. The resulting buckled graphene opens a band-gap greater than 0.7eV in the otherwise continuous metallic graphen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
0
27
1
Order By: Relevance
“…Thus, non-uniform strains could be induced by placing PE on nanoscale patterns and on nanoparticles [21,22], or by pinning the 2D layer onto a substrate [23].…”
mentioning
confidence: 99%
“…Thus, non-uniform strains could be induced by placing PE on nanoscale patterns and on nanoparticles [21,22], or by pinning the 2D layer onto a substrate [23].…”
mentioning
confidence: 99%
“…Instead, the nitrogen remains between the graphene and the SiC surface as schematically illustrated in Fig. 1(a) [5]. It is known from previous studies that the nitrogen bonding between the first graphene layer and the SiC causes the graphene to buckle as shown in Fig.…”
Section: N-gr Ribbon Growthmentioning
confidence: 98%
“…Furthermore, FETs built from monolayer C-face graphene have shown the highest operating frequencies of any graphene-based devices [4]. New experiments on C-face SiC have recently shown that graphene grown from a C-face surface seeded with nitrogen (N-Gr) produces a large band gap form of graphene [5]. The nitrogen induced gap is thought to be a result of a strain gradient caused by a graphene-nitrogen-SiC bond that forces the graphene to buckle [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations